2018
DOI: 10.1371/journal.pone.0208023
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with medical support in women with endometriosis

Abstract: Endometriosis affects various aspects of women’s lives. We searched for predictors for patient satisfaction with medical support (PSwMS) in women with endometriosis. The study was designed as a multi-centre retrospective cohort study. We approached women with histologically confirmed endometriosis from 2010 until 2016, comparing women satisfied to women dissatisfied with medical support. We analysed data on characteristics of endometriosis, PSwMS and the influence of disease characteristics on PSwMS. Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
4
31
0
1
Order By: Relevance
“…Rowe et al found three domains of endometriosis care that could influence patient satisfaction with endometriosis care: (i) information that meets patients’ needs; (ii) being heard with empathy and respect; and (iii) technical competence. Similar domains were also found by two previous questionnaire studies investigating patient satisfaction ( Lukas et al , 2018 ; Wygant et al , 2019 ).…”
Section: Introductionsupporting
confidence: 87%
“…Rowe et al found three domains of endometriosis care that could influence patient satisfaction with endometriosis care: (i) information that meets patients’ needs; (ii) being heard with empathy and respect; and (iii) technical competence. Similar domains were also found by two previous questionnaire studies investigating patient satisfaction ( Lukas et al , 2018 ; Wygant et al , 2019 ).…”
Section: Introductionsupporting
confidence: 87%
“…Treatment is based on surgical procedures and/or hormone therapy. It aims to control the symptoms, and unfortunately, it does not always bring the expected long-term result [ 1 , 2 , 3 , 4 , 5 , 31 , 32 , 33 ]. Interesting in this context are the self-care measures for chronic diseases, which are an essential aspect in strengthening health, alleviating symptoms, and preventing the consequences of diseases, which can also apply to women with endometriosis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 Giving women sufficient knowledge and encouraging them to participate in care can be effective ways to increase satisfaction with care. 28 However, this presumes that women and physicians are in cooperation, sharing knowledge and experiences. It is a balancing act, protecting women from worries or involving them in caring actions.…”
Section: Discussionmentioning
confidence: 99%